2020
DOI: 10.18632/aging.103413
|View full text |Cite
|
Sign up to set email alerts
|

Infertility induced by auxin in PX627 Caenorhabditis elegans does not affect mitochondrial functions and aging parameters

Abstract: Caenorhabditis elegans is widely used for aging studies. 5-Fluoro-2´-deoxyuridine (FUdR) is commonly used to control offspring. While larvae are stopped from further development, also mitochondrial DNA and function may be affected. Since mitochondria and longevity are closely related, the use of FUdR may falsify possible studies. PX627, an auxin inducible infertility strain to control offspring, allows mitochondrial investigations during senescence without FUdR toxicity. Longevity and health parameters were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Indole at a concentration range of 0.1 – 0.25 mM was found to promote healthy aging (Sonowal et al, 2017) while at concentrations higher than 0.5 mM it was found to reduce survival (Lee et al, 2017). By contrast, 1 mM IAA was reported to have no effect on either lifespan or mitochondrial functions (Dilberger et al, 2020; Kasimatis et al, 2018). The reasons for these different responses when using closely-related molecules are unclear.…”
Section: Resultsmentioning
confidence: 96%
“…Indole at a concentration range of 0.1 – 0.25 mM was found to promote healthy aging (Sonowal et al, 2017) while at concentrations higher than 0.5 mM it was found to reduce survival (Lee et al, 2017). By contrast, 1 mM IAA was reported to have no effect on either lifespan or mitochondrial functions (Dilberger et al, 2020; Kasimatis et al, 2018). The reasons for these different responses when using closely-related molecules are unclear.…”
Section: Resultsmentioning
confidence: 96%
“…Indole at a concentration range of 0.1–0.25 mM was found to promote healthy aging ( Sonowal et al, 2017 ) while concentrations higher than 0.5 mM were found to reduce survival ( Lee et al, 2017 ). By contrast, 1 mM IAA was reported to have no effect on either lifespan or mitochondrial functions ( Dilberger et al, 2020 ; Kasimatis et al, 2018 ). The reasons for these different responses when using closely-related molecules are unclear.…”
Section: Discussionmentioning
confidence: 96%
“…In PX627, TIR1 expression is driven in the germline using the germ-cell specific pie-1 promoter . PX627 has been characterized for mitochondrial and health span parameters but mainly in comparison to the effects produced by fluoro-deoxy uridine (fUDR), an alternative sterility-induction treatment ( Dilberger, et al, 2020 ). Dilberger et al found PX627 to show similar lifespan upon supplementation with 1 mM auxin versus FUdR ( Dilberger, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…PX627 has been characterized for mitochondrial and health span parameters but mainly in comparison to the effects produced by fluoro-deoxy uridine (fUDR), an alternative sterility-induction treatment ( Dilberger, et al, 2020 ). Dilberger et al found PX627 to show similar lifespan upon supplementation with 1 mM auxin versus FUdR ( Dilberger, et al, 2020 ). However, Kasimatis et al found that the strain exhibited lower late life mortality on auxin as compared to unsupplemented animals ( Kasimatis, et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation